Opportunistic infections in hospitalized HIV-infected adults in Ho Chi Minh City, Vietnam: a cross-sectional study. - Louie, J; Chi, N; Thao, L; Quang, V; Campbell, J; Chau, N; Rutherford, G; Farrar, J; Parry, C (2004)
The HIV epidemic is emerging rapidly in Vietnam. We studied the prevalence of opportunistic infections by performing clinical and microbiological investigations in 100 hospitalized HIV-infected adults in Ho Cho Minh City, Vietnam. The median CD4 count was 20 cells/mm(3) and in-hospital mortality was 28%. The most frequent diagnoses were oral candidiasis (54), tuberculosis (37), wasting syndrome (34), lower respiratory tract infection (13), cryptococcosis (9), and penicilliosis (7). Bacterial (other than tuberculosis) and parasitic infections were uncommon. Regional differences should be considered when deciding which diagnostic procedures and prophylactic measures to implement. In Vietnam, routine mycobacterial blood cultures do not provide greater yield than chest radiography and sputum and lymph node aspirate smears. Prophylactic trimethoprim/sulphamethoxazole against Pneumocystis jiroveci pneumonia may confer little benefit, and high rates of isoniazid resistance may affect the efficacy and feasibility of tuberculosis chemoprophylaxis. However, the usefulness of itraconazole prophylaxis for cryptococcosis and penicilliosis merits further consideration.